Demographic Comparison of Burn Emergency Only Visits and Admissions in an Urban Burn Center. Issue 3 (May 2016) - Kowal-Vern, Areta; Bokhari, Faran; Poulakidas, Stathis
Abstract : There are few publications about demographics of Emergency Department (ED) burn patient visits. The purpose of this study was to compare ED only burn patients with admitted patients in an urban burn center. This was a retrospective review (1999 to 2014) of a burn unit patient registry. Patients were seen either in the Emergency Room or Trauma Bay (ED-TB) by staff, who determined whether the patient required admission or not. During this period, of the 5936 burn injury ED-TB encounters, there were 3754 (63%) admissions and 2182 (37%) ED-TB only (evaluation and discharge) visits. The median age was 30 years, and the %TBSA in the ED-TB only versus admitted patients was 1% vs 4% TBSA, P < .0001. Both groups had mainly scalding injuries in the kitchen. The majority of the ED-TB only patients presented with upper extremity burns (40%), whereas admitted patients had burns in multiple areas (49%). Most of the ED-TB only patients (73%) came to the hospital themselves, 23% were transferred from other hospitals, and 2% each, direct from the scene and clinic. In contrast, 53% of admitted patients were transferred from other hospitals, 29% came in on their own, and 11% were brought in direct from the scene, or from the burn clinic (7%), P = .0001. This review suggests that the main reason for non-admission of ED-TB only patients was the severity of injury; ED-TB only patients had a significantly less severe %TBSA ( P < .0001), and fewer comorbidities compared to admitted patients.